La traducción eslovaca de El príncipe constante – la intención del traductor y el contexto de la traducción - Malovecký, Mojmír; Medveczká, Mária (Verbum – Analecta Neolatina, 2024)
Pavel Blaho translated Pedro Calderón de la Barca’s play El príncipe constante into Slovak on two separate occasions. The article seeks Blaho’s possible motive by analysing the translator’s intention based on the text of the second version of 1895 and contextualises the interest in this play in Central Europe by exploring a sequence of events related to historical characters and tracing the generational succession of translators, literati and philologists and their translations.